2018
DOI: 10.1103/physrevlett.121.196803
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Coupling of an Individual Magnetic Impurity to a Superconductor: Quantum Phase Transition and Transport

Abstract: The exchange scattering at magnetic adsorbates on superconductors gives rise to Yu-Shiba-Rusinov (YSR) bound states. Depending on the strength of the exchange coupling, the magnetic moment perturbs the Cooper pair condensate only weakly, resulting in a free-spin ground state, or binds a quasiparticle in its vicinity, leading to a (partially) screened spin state. Here, we use the flexibility of Fe-porphin (FeP) molecules adsorbed on a Pb(111) surface to reversibly and continuously tune between these distinct gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
116
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(128 citation statements)
references
References 41 publications
(48 reference statements)
9
116
2
1
Order By: Relevance
“…48 This ground state spin configuration can be altered by slight differences in the molecular ligand field or the interaction with the substrate as shown by YSR states observed on a related iron porphyrin molecule on Pb(111) substrate. 33 We have verified that the observed transitions result from inelastic spin excitations by acquiring the dI/dV spectra under an external magnetic field (B) perpendicular to the sample surface (see SI for details). The B-field dependence of the energies of the first and second feature is consistent with S = 1 with transverse anisotropy.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…48 This ground state spin configuration can be altered by slight differences in the molecular ligand field or the interaction with the substrate as shown by YSR states observed on a related iron porphyrin molecule on Pb(111) substrate. 33 We have verified that the observed transitions result from inelastic spin excitations by acquiring the dI/dV spectra under an external magnetic field (B) perpendicular to the sample surface (see SI for details). The B-field dependence of the energies of the first and second feature is consistent with S = 1 with transverse anisotropy.…”
mentioning
confidence: 64%
“…3,7,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The bulk of recent experimental work on YSR states on superconducting (SC) substrates has demonstrated that the strength of the exchange interaction J can be significantly influenced by a small change in the adsorption site of the impurity or by spacers between the impurity and substrate. 3,18,[25][26][27][28][29][30][31][32][33][34] with α proportional to J, α = πρJS/2, where ρ is the normal-state density of states of the substrate at the Fermi level and S is the impurity spin. The bound state results from the spin-dependent scattering of Bogoliubov quasiparticles on the impurity and is thus associ-ated with the longitudinal part of the exchange interaction, JS z s z , where s represents the spin-density of the substrate electrons at the impurity position.…”
mentioning
confidence: 99%
“…In a classical picture, the energy position E YSR of the YSR state with respect to E F depends mainly on the s-d-or Kondo exchange coupling J K of the local spin of the atom to the substrate conduction electrons. 34 For low J K , the peaks merge with the coherence peaks at the gap edge ∆, whereas for higher J K , they shift towards E F and eventually cross it, commonly referred to as a quantum phase transition 37 . For even higher J K , the in-gap states merge with the coherence peaks again.…”
mentioning
confidence: 99%
“…Remarkably, with increasing magnetic field, the spatial extension of the Shiba state increases significantly further.Shiba states were widely studied in two different types of systems: a) in STM measurements, when magnetic particles are deposited on the surface of a superconductor [34][35][36][37][38][39][40][41][42][43][44][45], and b) in nanocircuits, when a quantum dot is attached to the superconductor . The STM geometry allows for the spatial mapping of the Shiba state [34][35][36][37], but the strength of the coupling between the magnetic adatom and the substrate is mostly determined by the microscopic details and its tuning remains quite challenging [40,43]. In contrast, the quantum dot realization enables the tuning the energy of the Shiba state via the level position or the tunnel couplings by using external gate voltages [58,59].…”
mentioning
confidence: 99%